THE HEDONISM LIFESTYLE, FINANCIAL LITERACY AND FINANCIAL MANAGEMENT AMONG BUSINESS EDUCATION STUDENTS TO FINANCIAL MANAGEMENT - Putra, Pasca Dwi; Harahap, Khairunnisa; Rahmah, Seline Suci (Journal of Community Research and Service, 2020)
The problem of this research is the poor management of student finances. This study aims to determine how much influence the lifestyle of hedonism and financial literacy on student financial management. The population of this study includes all of the Business Education students batch of 2017 with a sample of 90 respondents. The research instrument test uses the validity and reliability test carried out with the SPSS 22 for Windows software application. Research data analysis techniques: normality test, linearity test, multicollinearity test, multiple linear, F-test using the SPSS software application. The result of this research show that hedonism lifestyle has a negative and significant effect on student financial management; financial literacy has a positive and significant effect on student financial management. The results of this study indicate that there is a significant influence on the lifestyle of hedonism and financial literacy on student financial management, both partially and simultaneously. Keywords: Hedonism Lifestyle; Financial Literacy; Financial Management.